A nanoelectromechanical-switch-based thermal management for 3-D integrated many-core memory-processor system - Huang, Xiwei (2012)
Tera-scale has become the recent interest for high-performance computing system. In order to increase bandwidth yet decrease power, 3-D integrated many-core memory-processor system is one of the most promising solutions. However, the increased power density and longer vertical heat-removal path in 3-D can result in thermal reliability concerns such as thermal runaway and thermal stability, which pose a significant barrier for tera-scale applications. Due to “green-switch” properties such as zero leakage current, infinite subthreshold slope, and temperature resilient behavior, nanoelectromechanical switches (NEMS) are explored in this paper to mitigate the thermal reliability issues for 3-D integrated many-core memory-processor system. The NEMS-based thermal management for 3-D integrated many-core memory-processor system is examined from device, circuit, and system levels, respectively. Moreover, one real-time thermal management is developed for improving system reliability with the use of NEMS-based thermal buffer and power gating. Experimental results show that our proposed approach can effectively prevent the thermal runaway and also maintain high thermal stability for 3-D integrated many-core memory-processor system.